Anticipated Regret in the Purchase of Secondhand and Counterfeit Product - Kurniawati, Masmira (JDM (Jurnal Dinamika Manajemen), 2019)
The purpose of this study is how consumers can minimizing negative emotion they will probably experience. One of negative emotion that consumers could experience is regret. When consumers develop a mechanism to anticipate future regret after buying decision, it is called anticipated regret. This research identifies how anticipated regret affects consumer choice between two risky buying decisions, which are counterfeit product and secondhand product. This research also investigates whether perceived risk mediates the effect of anticipated regret on consumers’ choice. Experimental design is used with 120 participants. The result of the analysis shows that anticipated regret significantly affects perceived risk, anticipated regret has negative significant effect toward purchase intention, and perceived risk also negatively affect purchase intention. The bootstrap results indicate that perceived risk mediates the effect of anticipated regret on consumers’ choice. Managerial implications and suggestions for future research then will be delivered.